2005
DOI: 10.1007/b107173
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobase-Containing Gelators

Abstract: Nucleobases are nitrogenous heterocyclic compounds and have high ability to form directionally controlled multiple intermolecular interaction, i.e., in-plane multiple hydrogen-bonding interactions and stacking interactions perpendicular to the plane. Here the recent development of nucleobase-containing low molecular mass gelators in aqueous and organic systems is reviewed, and the self-assemblies of nucleobase-containing small molecules and their arrangement within the gel are discussed from the molecular, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 74 publications
0
78
0
Order By: Relevance
“…All the intermediate products synthesised were purified by silica gel column chromatography and then fully characterised by 1 H and 13 C NMR spectroscopy and ESI mass spectrometry. Final compounds G1-G7, obtained from the corresponding nucleobase-protected precursors by a simple treatment with TFA (10 %) in CH 2 Cl 2 , followed by repeated co-evaporations from isopropanol until the excess TFA had disappeared completely, were identified on the basis of their NMR and ESI-MS spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the intermediate products synthesised were purified by silica gel column chromatography and then fully characterised by 1 H and 13 C NMR spectroscopy and ESI mass spectrometry. Final compounds G1-G7, obtained from the corresponding nucleobase-protected precursors by a simple treatment with TFA (10 %) in CH 2 Cl 2 , followed by repeated co-evaporations from isopropanol until the excess TFA had disappeared completely, were identified on the basis of their NMR and ESI-MS spectra.…”
Section: Resultsmentioning
confidence: 99%
“…liminary studies aimed at identifying new tools with the potential to profitably complement the lipophilic congeners recently studied by the research groups of G. P. Spada, [6][7][8][9] J. T. Davis [9][10][11][12] and K. Araki [13][14][15] , among others, further expanding the chemical diversity offered by nucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Araki and Yoshikawa recently introduced nonpolar and flexible alkylsilyl groups into 2'-deoxyguanosine to obtain efficient organogelators for alkanes. [21] From an in-depth structural analysis, they concluded that in these gels the basic structure is a sheetlike assembly: the supramolecular structure (see Figure 2) consists of anti-parallel G ribbons like in Figure 1e linked through two additional inter-tape hydrogen bonds between NH(2) and N(3) of the two guanines belonging to adjacent ribbons. Upon heating, a gel-toliquid-crystal phase transition is observed and has been ascribed to the selective cleavage of the inter-tape H-bonds.…”
Section: Introductionmentioning
confidence: 99%
“…11 Among these gelators, the biocompatible and biodegradable species are particularly popular for constructing hydrogels, such as nucleobases, 12 bile salts, 13 carbohydrates 14 and peptides, 15 as they can be safely used in biological applications. 16 Bile acids and their salts belong to not only important biological surfactants, but also small-molecule biological gelators that can act as solubilizers of cholesterol, bilirubin, and various fat-soluble vitamins in the intestine of vertebrates, including humans.…”
Section: Introductionmentioning
confidence: 99%